High-Voltage Ignition Circuit For Compressed Natural Gas Direct Injection Engine - Omar, Azimah (2007)

(untitled)
Ignition system of an internal combustion engine is an important part of the overall engine management system. It is a means to provide enough high-voltage, minimum around 20 kV to form an arc across the gap of a spark plug and to control the ignition timing. Thus, it can provide a right time to burn the air-fuel mixture inside the engine. With advances in technology, the ignition system has progressed from a contact point ignition system to an electronic ignition system and then to a digital distributorless ignition system. The increased growth of the ignition system design in both size and complexity has brought about the need for a simple and reliable ignition system to provide high-voltage output to be delivered to the spark plug and at the same time to adapt with the natural gas engine environment. Therefore, with the development of an economical and reliable ignition system, there is a growing interest in developing digital distributorless ignition system, which is programmable making it more flexible and superior to other conventional system. This thesis presents the development of an ignition circuit for a coil-on plug ignition system of a natural gas engine. The main specification of the circuit is the implementation of the ignition power-switching device at the primary side of the circuit to provide high switching speed to turn on and off the device. The chosen power-switching device was Insulated Gate Bipolar Transistor or IGBT, which is more suitable to be implemented inside the circuit design compared to other power-switching devices. The selected IGBT, IRGB14C40L are specifically design for a ignition applications and small engine ignition circuit. It has low saturation voltage and high self-clamped inductive switching energy. The modelling and optimization of the ignition IGBT parameters is done in the PSPICE software to fulfill the real ignition power-switching device requirements. The other specification of the circuit design is the implementation of the snubber circuit, which can provide over-voltage protection at the primary side of the power-switching device. Finally, the testing of the circuit is done by applying a control signal at the input source terminal or at the gate terminal of the ignition IGBT. The complete circuit design is integrated with the high-voltage ignition coil and a special designed long neck spark plug for the natural gas engine purpose. The circuit has been tested to make sure it can provide the desired voltage so it can ignite the mixture of the air and compressed natural gas in the right cylinder and at the right time. From the test results of the ignition circuit, it demonstrates that the performances of the ignition parameters such as the primary current and secondary voltage are highly affected by the device parameters like the ignition IGBT parameters, specifications of the high-voltage ignition coil as well as the control strategy of the switching-time to ignite the spark plug.